2015
DOI: 10.1186/s13071-015-0734-4
|View full text |Cite
|
Sign up to set email alerts
|

New adhesive traps to monitor urban mosquitoes with a case study to assess the efficacy of insecticide control strategies in temperate areas

Abstract: BackgroundUrban mosquitoes in temperate regions may represent a high nuisance and are associated with the risk of arbovirus transmission. Common practices to reduce this burden, at least in Italian highly infested urban areas, imply calendar-based larvicide treatments of street catch basins – which represent the main non-removable urban breeding site – and/or insecticide ground spraying. The planning of these interventions, as well as the evaluation of their effectiveness, rarely benefit of adequate monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
2
19
0
1
Order By: Relevance
“…albopictus and Cx. pipiens was strongly inhibited in diflubenzuron‐treated catch basins, and that diflubenzuron was more effective and persistent than pyriproxyfen formulations against Ae. albopictus .…”
Section: Chemical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…albopictus and Cx. pipiens was strongly inhibited in diflubenzuron‐treated catch basins, and that diflubenzuron was more effective and persistent than pyriproxyfen formulations against Ae. albopictus .…”
Section: Chemical Methodsmentioning
confidence: 99%
“…albopictus and had a more effective residual effect on vegetation than an α ‐cypermethrin formulation. In Italy, Caputo et al observed a reduction in Ae. albopictus abundance during the major phase of the population expansion after low‐volume application of permethrin and pyrethrum.…”
Section: Chemical Methodsmentioning
confidence: 99%
See 3 more Smart Citations